2015
DOI: 10.1002/2014jd022341
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological extremes in hyperarid regions: A diagnostic characterization of intense precipitation over the Central Arabian Peninsula

Abstract: Aridity is typically associated with deep and dry daytime boundary layers, stable nighttime stratification, divergent flows, and limited large‐scale moisture advection. All these factors are paramount in regulating the hydroclimatology of hyperarid regions, resulting in extremely intermittent—and often intense—local precipitation patterns. However, the link between synoptic‐scale forcing and intense precipitation over arid regions has been scarcely investigated in the literature and still remains exceedingly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 82 publications
4
34
0
Order By: Relevance
“…In both arid and semiarid climate simulations, the frequency of rainfall occurrence is kept low ( λ = 0.1/day) to maximize the capacity of rain events to wash away salts. This assumption is consistent with the predominantly convective nature of dryland precipitation, characterized by extremely sporadic, short‐duration, and intense events (Kumar et al, ; Warner, ).…”
Section: Resultssupporting
confidence: 82%
“…In both arid and semiarid climate simulations, the frequency of rainfall occurrence is kept low ( λ = 0.1/day) to maximize the capacity of rain events to wash away salts. This assumption is consistent with the predominantly convective nature of dryland precipitation, characterized by extremely sporadic, short‐duration, and intense events (Kumar et al, ; Warner, ).…”
Section: Resultssupporting
confidence: 82%
“…In this respect, further analysis of the precipitation variability using all available data will be desirable. We noted above that Mekasha et al (2014) and Kumar et al (2015) reported the growing intensity of heavy precipitation over the East African Rift Valley and the Arabian Peninsula. The mechanisms through which increased moisture export can affect precipitation over the adjacent continents are quite complicated, given that the moisture recycling in this region is modulated by various atmospheric processes in a heavily undersaturated atmosphere.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Over the Arabian Peninsula, precipitation, while very rare, has undergone downward changes during the last decade, as reported by station data (AlSarmi andWashington 2011, 2014) and the Tropical Rainfall Measuring Mission (TRMM; Almazroui 2011). Nevertheless, moisture transports from the Red Sea and the Arabian Sea result in heavy precipitation events even over the hyperarid Arabian Peninsula (Kumar et al 2015). While Viste et al (2013) reported an intensification of drying conditions over northeastern Africa, Mekasha et al (2014) demonstrated that heavy precipitation events intensified over the last three decades, particularly in the East African Rift Valley.…”
Section: Introductionmentioning
confidence: 94%
“…They also propagate over long distances and can contribute to teleconnecting remote regions of the atmosphere (Chang and Yu, 1999;Niranjan Kumar and Ouarda, 2014). For example, Chang and Yu (1999) have shown that during December-January-February in the Northern Hemisphere, the Rossby wave packets are most coherent along a band that extends from northern Africa through southern Asia (maximum coherence) into the Pacific storm track.…”
Section: K Niranjan Kumar Et Al: Extratropical Rossby Waves and Sumentioning
confidence: 99%
“…The background flow dictates the propagation of Rossby waves, which are linked to the strong vorticity gradient around the tropopause in extratropics (e.g., Hoskins and Ambrizzi, 1993;Branstator, 2002;Schwierz et al, 2004b). Theoretical and observational studies along with idealized numerical experiments have indicated that topographically and diabatically generated vortex anomalies at upper and lower levels can serve as triggers for Rossby waves propagating into the extratropics (Sardeshmukh and Hoskins, 1988;Hoskins and Karoly, 1981;Schwierz et al, 2004a;Niranjan Kumar and Ouarda, 2014). Also, a significant role in the amplification of the waves is played by the diabatic processes as demonstrated in a previous case studies (Massacand et al, 2001).…”
Section: Introductionmentioning
confidence: 99%